Executive Committee Minutes 2007-04-19 - Academic Senate:::::::::
Resolution from APC on changing Schools to Colleges, Communications Department shift to 4 units, Constitution and By-Laws revision: inclusion of VP of SAEM and CFA rep, Revision to Wine Business Masters, Resolution on Virginia Tech Tragedy